Hydrozoan diversity on hard bottom in Kongsfjorden, Svalbard - Voronkov, Andrey; Stepanjants, S.D.; Hop, Haakon (Journal of the Marine Biological Association of the United Kingdom, 2010)
This article is part of Andrey Voronkovs doctoral thesis, available in Munin at http://hdl.handle.net/10037/6381 Hydroids in Kongsfjorden, Svalbard, were studied on five hard-bottom transects along gradients of environmental conditions from the glacier at the fjord’s head to the fjord’s mouth at depth-range 0–30 m. Hydrozoa colonies are widely distributed on rock and gravel substrata in Kongsfjorden. In general, however, hydroids are not dominant or subdominant in zoobenthic communities. The exception is Symplectoscyphus tricuspidatus var. acuminatus, colonies of which were sometimes abundant enough to determine the community structure and characteristics of benthic diversity. Of the 23 species recorded in this study, Laomedea flexuosa, Phialella quadrata and Halecium tenellum as well as representatives of family Stylasteridae were recorded from Svalbard waters for the first time. Hydroid diversity was highest in the zoobenthic community structured by branched bryozoans. The abundance and distribution of hydroids were reduced, to some extent, in the inner part of the fjord compared to the outer fjord. Species richness of hydroids was high at shallow depths, decreased at around 15 m and then increased again to 30 m depth. Species with Low-boreal–Arctic and Panoceanic distributional ranges were the most frequently occurring species. Depth, type of background substratum and amount of silt on its surface were the main factors influencing hydroid distribution. Description of all recorded taxa distributions together with data on their habitat and associations in zoobenthic communities are presented in an Appendix.